PENGARUH OPINI GOING CONCERN, AUDIT DELAY, DAN PERTUMBUHAN PERUSAHAAN TERHADAP AUDITOR SWITCHING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PROPERTI & REAL ESTATE TERDAFTAR DI BEI TAHUN 2014-2019) - Siti Nurlatifah; Esti Damayanti (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study aims to determine the partial or simultaneous effect of going concern opinion, audit delay, and company growth on auditor switching in real estate and property sub-sector manufacturing companies. This study uses a quantitative quantitative approach, aiming to determine the relationship between two or more. The data used is secondary data, namely financial reports and annual reports downloaded from the official website of the IDX, namely www.idx.co.id. The population of this research are Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2014-2019 as many as 65 companies. Samples were taken using purposive sampling technique as many as 17 companies in 6 years so as to produce 102 units of analysis. The data analysis technique used SPSS version 25 program in the form of descriptive statistics and logistic regression. The test results show that going concern opinion has a positive and significant effect on auditor switching, audit delay cannot affect auditor switching on auditor switching, company growth cannot affect auditor switching on auditor switching, as well as going concern opinion, audit delay, and company growth simultaneously. have an effect on auditor switching. The novelty of this study answers the gap of previous research, using different variables from previous researchers and a different time span from previous years.